The Influence of Manichaeism on Augustine of Hippo as a Spiritual Mentor - McCann, Christine (Cistercian studies quarterly, 2009)
The article explores how Manichaeism influenced Augustine of Hippo as a spiritual teacher. Based on Paulinus of Nola's letters to Augustine became a Manichean in 372/3 and remained associated until he moved to Milan, Italy in 384. These letters demonstrated as evidence his activities as a spiritual mentor. They also illustrated that he believed Manichaeans in general and he himself had taken great pride in their false wisdom and their abilities to enlist more people into the sect.